Clinical profile of patients with juvenile idiopathic arthritis - Paudyal, Buddhi Prasad; Gyawalee, Madhu Education (Journal of Patan Academy of Health Sciences, 2016)
Introductions: Juvenile idiopathic arthritis (JIA) is a heterogeneous group of disorders with different manifestations. There is lack of data locally. In this study, we describe the clinical profile and functional outcome of patients with JIA attending two rheumatology clinics in Lalitpur, Nepal. Methods: This cross sectional study was conducted at Patan Hospital and Aarogya Health Home, Lalitpur, Nepal. The medical records of patients with juvenile arthritis during Jan 2013 to Dec 2015 were retrospectively reviewed for clinical profile and functional outcome of the disease. Results: A total of 81 patients with arthritis, diagnosed before age 16 years, were seen during this period. Seventy-eight patients with JIA included 41 males and 37 females. Mean age of onset was 9.21 years. Polyarticular JIA was seen in 32 (42.2%), oligoarticular in 24 (30.7%), enthesitis-related in 13 (16.6%), and systemic-onset in 6 (7.7%) patients. Systemic complications were seen in 14 (17.9%) cases; five cases had uveitis; joint deformities were present in 28 (35.8%); sixty-seven (86%) children continued their education; functional limitation (Steinbrocker’s functional class III and IV) was seen in 4 (5.1%). One child with oligoarticular JIA died. Conclusions: The clinical profile of JIA in Nepalese patients is similar to studies from other parts of the world. During the short follow up, functional limitation was not a major problem. Journal of Patan Academy of Health Sciences, Vol. 3, No. 1, 2016. page: 10-14